β2-glycoprotein I Binding to Platelet Microparticle Membrane Specifically Reduces Immunoreactivity of Glycoproteins IIb/IIIa - Vallar, Laurent; Regnault, Véronique; Latger-Cannard, Véronique; Lecompte, Thomas (Thrombosis and Haemostasis, 2001)
We have investigated β2-glycoprotein I (β2GPI) binding to platelet-derived microparticles (PMP) and its effect on GPIIb/IIIa. PMP were isolated from washed human platelets after stimulation with A23187, and analyzed by surface plasmon resonance spectroscopy. β2GPI as well as activated protein C (APC) or annexin V bound to PMP-coated sensorchips, demonstrating exposure of anionic phospholipids on immobilized PMP. β2GPI binding was impaired by calcium and occurred in a concentration-dependent manner with apparent kon = 2.6104 M-1.s-1 and koff = 4.410-3 s-1, corresponding to a KD value of 1.710-7 M. When analyzed by flow cytometry, the binding of certain mAbs specific for GPIIb and/or GPIIIa was reduced in the presence of β2GPI but not of APC or annexin V, whereas the binding of anti-GPIb or anti-P-selectin mAbs, or of soluble fibrinogen remained unchanged. These results suggest a broad but specific influence of β2GPI on GPIIb/IIIa immunoreactivity, and indicate that β2GPI may act as a modulator of GPIIb/IIIa-dependent functions of PMP.
Keywords: β2-glycoprotein I; platelet microparticles; glycoproteins IIb/IIIa